Keseimbangan Aktifitas Fisik Siswa Sekolah Berbasis Pesantren - Topo Yono; M.Fikrul Ihtiar; Dyanisaf Ramadhani (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2022)
The imbalance of physical activities will provide a problem on students’ fitness in carrying out learning activities. The physical fitness quality of students of Islamic boarding school is the focus of this research to describe clearly how the balance of students’ physical activities and how their physical fitness. This research is descriptive research with qualitative approach. The technique of collecting student fitness data through Multistage Fitness Test (MFT) to determine the value of VO2Max. The respondents were 27 active students of MTs Islamic Boarding School Sumberwringin. Data analysis techniques using percentages based on physical fitness norms from Davis et al. The results showed that the students’ physical fitness level of MTs Islamic Boarding School Sumberwringin was in the moderate category as the result of good enough balance in physical activities.